Citizen participation in public administration: investigating open government for social innovation. (11th March 2019) - Schmidthuber, Lisa; Piller, Frank; Bogers, Marcel; Hilgers, Dennis
Abstract : In recent years, public sector organizations have increasingly focused on citizen contribution by adopting instruments known from open innovation. By collaborating with the periphery and leveraging external knowledge, government institutions initiate social innovation and stimulate a positive change for society. This article examines the involvement of citizens in an ideation platform initiated by a local government and investigates the motivations affecting participation intensity. Drawing on self‐determination theory, we analyze what motivates citizens to participate in an open government platform and how these motivations influence participation quantity. Based on a survey among platform users and the analysis of usage data from the platform operator, we find that motivations of citizen participation in public administration greatly vary across forms of participation. Whereas, intrinsic motivation is positively associated with producing and consuming platform content, external and introjected regulation negatively relate to individuals' active contribution. At the same time, external regulation is positively associated with evaluation behavior.